EXPLORING THE FACTORS INFLUENCING CLASS XI- XII PRIVATE COLLEGE STUDENTS’ ATTITUDES TOWARD ENGLISH AS A SECOND LANGUAGE (Al-Aasar, 2025)
This study investigates the factors influencing students’ attitudes towards learning English as a second language (ESL) in private colleges in Pakistan. Using a qualitative research approach, the study integrates to explore learners’ motivation, challenges, and perceptions. A sample of 20 students from Hayat Girls College and Superior College in Hyderabad was selected through purposive sampling. Data of the study was collected through semi-structured interviews, and was analyzed using thematic analysis. The thematic analyses highlighted the role of sociocultural influences and classroom dynamics with students expressing a preference for interactive and practical teaching methods. These findings suggest that while English is viewed as essential for academic and professional growth, addressing key barriers such as anxiety, grammar, and speaking practice for improving ESL learning experience.